Specyficzne problemy ekonomiczne kapitalistycznych krajów pozostających na niskim poziomie rozwoju - Gulcz, Mieczysław (Wydział Prawa i Administracji UAM, 1979)
The elaboration is a synthesis of a rich output of Marxist thought in the scope of problems of economic under-development. This sphere is — according to the author — insufficiently considered in lectures on political economy. A variety of arguments have been pointed out in the introduction speaking in advocacy of placing those questions into the lecture on political economy. They can be considered neither in the course of analysis of the beginnings of development of countries being high developed today, nor within the scope of analysis of the period of transition to socialism. Accepting heterogeneous character of the discussed group of countries it is unquestionable that they are characterized by under-development, understood as a set of phenomena mutually combined and conditioned. They are presented in a static approach in the first part of the elaboration. After characteristics of features of under-development the author points out that they are both its effects and reasons. The other three parts of the elaboration present general principles of a strategy in the process of underdevelopment overcoming in a dynamic approach. The fundamental role is attributed by the author to internal potentialities. On the ground of presentation of potential economic surplus the. necessity and methods of reconstruction of socio-economic structures is pointed out. The most important factors which help to internal efforts are seen by the author in integrated actions of economically developed countries (capitalist and socialist ones) and of undeveloped countries in the sphere of re-arranging the situation of the last on the world market and in the sphere of rendering and using foreign economic aid.
Planowanie regionalne w krajach azjatyckich: diagnoza stanu i potrzeb
Keywords: WPiA